Efficient Conjugation of Oligosaccharides to Polymer Particles through Furan/Maleimide Diels–Alder Reaction: Application to the Capture of Carbohydrate‐Binding Proteins. (7th December 2016) - Petrelli, Antoine; Samain, Eric; Pradeau, Stéphanie; Halila, Sami; Fort, Sébastien
Abstract: Glycan–protein interactions play a crucial role in physiological and pathological events. Hence, improving the isolation of carbohydrate‐binding proteins (i.e., lectins and anti‐glycan antibodies) from complex media might not only lead to a better understanding of their function, but also provide solutions for public health issues, such as water contamination or the need for universal blood plasma. Here we report a rapid and efficient method for producing carbohydrate‐based affinity adsorbents combining enzymatic synthesis and metal‐free click chemistry. Both simple and complex glycans (maltose, blood group antigens A, B, and H) were readily modified by the addition of a furyl group at the reducing end without the need for protecting groups and were then efficiently conjugated to maleimide‐activated Sepharose particles through Diels–Alder cycloaddition. These neoglycoconjugates showed high efficiency for the purification of lectins (concanavalin A and Ulex europaeus agglutinin), as well as for the capture of anti‐A and anti‐B blood group antibodies, opening new prospects for glycoproteomics and for the development of universal blood plasma. Abstract : Fishing for carbohydrate‐binding proteins : A protocol for the chemoselective modification of oligosaccharides and their conjugation through Diels–Alder cycloaddition has been developed. Carbohydrate affinity adsorbents were efficiently produced and used for the purification of lectins and for the capture of anti‐blood‐group antibodies.